(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
The paper deals with the European arrest warrant in the case law of Croatian courts and presents the principles of mutual recognition and trust, as well as the principle of the verification of double criminality which has attracted a lot of attention in professional circles in the area of international judicial cooperation in criminal matters. The introductory part of the paper addresses the importance of this instrument as the cornerstone of judicial cooperation in criminal matters between EU Member States. This is followed by an analysis of the fundamental principles, specifically the principle of mutual trust as a structural principle of EU constitutional law, its origin and context in the light of the decisions rendered by the Supreme Court of the Republic of Croatia and the Constitutional Court of the Republic of Croatia. The central part of the paper analyses the principle of verification of double criminality and the implementation of that principle in the process of executing the European arrest warrant, and relates that principle to the mandatory and optional grounds for non-execution of the warrant. A brief overview is then provided of the execution of the warrant with reference to the decisions of the Supreme Court of the Republic of Croatia, and the paper ends with an evaluation of the significance of the principle of mutual recognition in criminal matters as exemplified by the judgments of the Court of Justice of the European Union.